Case Report: Anti-ADAM23 antibody: an overlooked autoantibody against VGKC-complex in autoimmune encephalitis - Ni, Pinfei; Bai, Lin; Jiang, Nan; Fan, Siyuan; Yao, Ming; Ren, Haitao; Guan, Hongzhi (Frontiers in Immunology, 2025)
ObjectivesAntibodies against voltage-gated potassium channel (VGKC) complexes include anti-LGI1 and anti-CASPR2. Anti-ADAM23 antibodies have not been previously reported in autoimmune encephalitis (AE).Case reportWe report a 71-year-old female patient who presented with rapidly progressive short-term memory loss, psychobehavioural abnormalities, and impaired consciousness. Six months earlier, she had recovered from herpes simplex encephalitis (HSE). Cerebrospinal fluid (CSF) analysis suggested lymphocytic inflammation. AE was considered after the exclusion of HSV reactivation and other infectious etiologies. A comprehensive screening for commercially available autoimmune and paraneoplastic antibodies yielded negative results. A tissue-based assay (TBA) of CSF revealed a pattern of neuropil reactivity (neuropil pattern, suggesting the presence of neuronal surface antibodies (NS-Ab). A laboratory-developed antibody panel screening using a cell-based assay (CBA) identified an anti-ADAM23 antibody. Immunofluorescence staining showed that ADAM23 colocalized with Tuj1, which is expressed on the surface of neurons. Subclass analysis revealed that the anti-ADAM23 antibody predominantly belonged to the IgG4 subclass. Finally, the patient was diagnosed with an anti-ADAM23 antibody-associated AE. During the early stages of the disease, the patient underwent several courses of intravenous immunoglobulin (IVIg) with limited efficacy. Following the addition of high-dose methylprednisolone pulse therapy, the patient's consciousness improved from coma to stupor and the seizures were relieved.ConclusionWe propose that anti-ADAM23 antibody, a previously overlooked autoantibody targeting the VGKC complex, may have diagnostic significance for autoimmune encephalitis.